(untitled) (Communications in Computational Physics, 2020)
A new method is proposed to simulate a coupled air-water two-layer turbulent channel flow. A numerically effective dynamic viscosity is implemented to calculate the viscous momentum flux at the interface, leading to a strong-coupling scheme for the evolution of air and water motions. The direct numerical simulation results are compared with those in the literature obtained from a weak-coupling scheme. It is discovered that while the turbulence statistics of the air phase based on the strong- and weak-coupling schemes are close to each other, the results on the water side are influenced by the coupling approach, especially near the water surface.